2015
DOI: 10.1007/s10995-015-1775-1
|View full text |Cite
|
Sign up to set email alerts
|

The Louisiana Family Opportunity Act Medicaid Buy-in Program

Abstract: The FOA program thus appears to be filling a niche in coverage needs among families of children with disabilities in Louisiana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…However, the current study suggests that policy and administrative changes are needed to improve overall satisfaction with this particular Medicaid Buy-In program and strengthen access to care for children with disabilities. While these results are not currently generalizable to other Medicaid Buy-In programs such as the Family Opportunity Act Medicaid Buy-In program, which has income limits (Bachman et al, 2015), the family perspectives presented here may provide a framework for thinking about how Medicaid Buy-In programs can best meet the needs of children with disabilities while providing much-needed financial relief to their families.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, the current study suggests that policy and administrative changes are needed to improve overall satisfaction with this particular Medicaid Buy-In program and strengthen access to care for children with disabilities. While these results are not currently generalizable to other Medicaid Buy-In programs such as the Family Opportunity Act Medicaid Buy-In program, which has income limits (Bachman et al, 2015), the family perspectives presented here may provide a framework for thinking about how Medicaid Buy-In programs can best meet the needs of children with disabilities while providing much-needed financial relief to their families.…”
Section: Discussionmentioning
confidence: 90%
“…There are various approaches to defining ‘access’ to health care ranging from the ability to pay for services to entry into and utilization of services and health-seeking behaviors (Bethell et al, 2008; Davidoff, 2004; Honberg et al, 2005; Kogan et al, 2005; McPherson et al, 1998; Yu et al, 2008). For children with disabilities, who may use a wide array of high-cost health-care and supportive services (Bachman et al, 2015), access to care will vary not only in accordance with diagnosis and severity, but also in a family’s ability to pay for these services (Penchansky and Thomas, 1981).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of the 15 studies (n = 8) used a cross-sectional research design, and collected or analyzed one wave of data (e.g., Bachman et al, 2015;Cook et al, 2004;Nebbitt et al, 2014). One study used a longitudinal design to collect 17 waves of annual data over a 17-year study period (Gavin et al, 2011), and six studies used two waves of data (e.g., pre-and post-test design) to examine the relationship between welfare participation and depression over time (e.g., Knab et al, 2006;Pande, 2014;Sullivan & Decoster, 2001).…”
Section: Characteristics Of Research Data and Study Designsmentioning
confidence: 99%
“…Of the 15 reviewed reports, five studies reported multiple welfare programs (e.g., Medicaid, SSI, AFDC, TANF, or WIC; Bachman et al, 2015;Buckner et al, 1999;Cook et al, 2004;Dosreis et al, 2001;Knab et al, 2006). Two studies focused on a general concept of welfare (e.g., any types of welfare programs; Go, 1999;Rhee et al, 2005).…”
Section: Welfare Programsmentioning
confidence: 99%